Terrorism and the limitation of rights : the ECHR and the US constitution - Sottiaux, Stefan (Human rights law in perspective, 2008)
Taking as a starting point the widely accepted view that states confronted with terrorism must find a proper equilibrium between their respective obligations of preserving fundamental rights and fighting terrorism effectively, this book seeks to demonstrate how the design and enforcement of a human rights instrument may influence the result of that exercise. An attempt is made to answer the question how a legal order''s approach to the limitation of rights may shape decision-making trade-offs between the demands of liberty and the need to guarantee individual and collective security. In doing.